Endless mode: Exploring the procedural rhetoric of a Black Lives Matter-themed newsgame. (June 2020) - Richardson, Allissa V
A week after the back-to-back police shootings of Philando Castile and Alton Sterling in early July 2016, a game developer, who goes by the screen name Yvvy, sat in front of her console mulling over the headlines. She designed a newsgame that featured civilian–police interactions that were plucked from that reportage. She entitled it Easy Level Life. The newsgame is fashioned in what developers call 'endless mode', where players are challenged to last as long as possible against a continuing threat, with limited resources or player-character lives. This case study explores the procedural rhetoric of Easy Level Life to investigate how it condemns police brutality through play. Using Teun van Dijk's concept of 'news as discourse' as the framework, I found that this newsgame followed the narrative structure of a traditional newspaper editorial very closely. I explain how the situation–evaluation–conclusion discursive model best describes how Easy Level Life conveys its political ideologies. I conclude by suggesting that this discursive model should perhaps become a benchmarking tool for future newsgame developers who aim to strengthen their arguments for social justice.